PROBLEMATIKA PEMBELAJARAN MAHĀRA KITĀBAH: STUDI KASUS MAHASISWA PENDIDIKAN BAHASA ARAB FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS ISLAM NEGERI SUMATERA UTARA - Bebi Khairani; Citra Sukma Ayu; Mita Atiqah Ginting; Siti Saidah; Sahkholid Nasution (Yayasan Haiah Nusratul Islam, 2024)
In Arabic, there are four special skills, namely mahārah istimā, mahārah kalām, mahārah qirā'ah and mahārah kitābah. In understanding each mahara, there are of course its own difficulties or problems, especially in studying the mahara kitabah. In this research, the author will discuss Mahārah Kitābah, namely the problem of learning mahārah kitābah which often occurs among students, especially UIN SU Medan Arabic Language Education students class. This research uses qualitative methods with data collection techniques through interviews and the data analysis techniques used are qualitative descriptive. The results that the author got were that students of Arabic Language Education at the State Islamic University of North Sumatra had problems learning mahārah kitābah. Students find it difficult to write texts or explanations given by lecturers in Arabic, this is because some of them have educational backgrounds that do not support Arabic language proficiency, such as high school and vocational school